The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.5513/jcea01/18.4.1953
|View full text |Cite
|
Sign up to set email alerts
|

The effect of feed additives in pheasants fattening: A review

Abstract: Fattening pheasants for the production of quality meat is a relatively recent development. With its high protein and low fat content, meat of pheasant is a highly nutritious food whose value exceeds that of broiler chickens meat. Despite the fact that the intensive rearing of pheasants has developed relatively quickly in recent years, information on the fattening capabilities and slaughter values of pheasants is often insufficient in the current literature. The length of the fattening period also differs in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
10
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 33 publications
0
10
0
Order By: Relevance
“…Its dietary value is very high and corresponds to the demands of modern man for nutrition (Hell et al, 2008). For the last years, poultry breeding became the most extensively developing branch of animal husbandry (Genchev et al, 2008). Common Pheasant (Phasianus colchicus) is bred on farms for hunting purposes in many countries (Torres et al, 1995;Canning, 2005;Gonzáles-Redondo and García-Domínguez, 2012;Hrabčáková et al, 2013b).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Its dietary value is very high and corresponds to the demands of modern man for nutrition (Hell et al, 2008). For the last years, poultry breeding became the most extensively developing branch of animal husbandry (Genchev et al, 2008). Common Pheasant (Phasianus colchicus) is bred on farms for hunting purposes in many countries (Torres et al, 1995;Canning, 2005;Gonzáles-Redondo and García-Domínguez, 2012;Hrabčáková et al, 2013b).…”
Section: Introductionmentioning
confidence: 99%
“…These proteins have an extraordinary biological value and are known to be highly used in the construction of human body proteins (Vodňanský et al, 2009). Pheasant meat is characterized by high nutritive value, as evidenced by high protein contents of breast (23.5-25.2%) and leg muscles (19.4-22.7%), and low proportion of fat (0.6-1.1%), especially in breast muscles (Večerek et al, 2005;Kuźniacka et al, 2007;Gašparovič et al, 2017) and 2.0-5.1% in leg muscles (Večerek et al, 2005). In terms of fat, the meat of the pheasant contains the highest proportion of unsaturated fatty acids -70.67 g.100 g -1 of total fatty acids (Vodňanský et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…This knowledge leads to the search for new solutions in chelate production and optimisation of the diet in mineral components, in order to improve the quality and value of breeding indicators and characteristics of farmed birds, including pheasants. Experimental modification of the proportion of mineral components in the diet has been undertaken by replacing inorganic with organic forms (6,17,24,40,47,52). The studies to date on the replacement of calcium, iron, zinc and copper salts with glycine chelates have shown a significant impact on pheasant production results.…”
mentioning
confidence: 99%
“…In turn, the replacement of vitamin D3 with calcitriol (active form of vitamin D -1.25-dihydroxycholecalciferol) resulted in higher phosphorus content and weight gain in males, as well as increases in magnesium and potassium content in muscles (18). These benefits prompted attempts to modify the pheasant diet composition to improve the quantity and quality of eggs, their hatchability and chemical composition, and their nutritional value (8,16,17,20,24,26,34,42,47).…”
mentioning
confidence: 99%
“…The high economic interest encourages producers to use alternative types of food additives in farm animal production which, however, need to be tested first (Vizzari et al 2014;Andrejcakova et al 2016;Russo et al 2019;Shah et al 2020). Studies on the use of HAs in livestock nutrition have confirmed their positive effects on animal growth, yield and reproduction (Ji et al 2006;Agazzi et al 2007;Cusack 2008;Wang et al 2008;Gasparovic et al 2017;Sladecek et al 2018). The beneficial effects of HAs on selected production indicators, such as the increased gains, feed conversion, egg production, egg weight and the decreased mortality have been confirmed in poultry (Kocabagli et al 2002;Yoruk et al 2004;Kucukersan et al 2005;Avci et al 2007;Ozturk et al 2010;Samudovska and Demeterova 2010;Ozturk et al 2012;Supriyati et al 2015;Arpasova et al 2016;Lala et al 2016).…”
mentioning
confidence: 99%